Differential branching fraction and angular analysis of the decay B0s → ϕμ+μ− - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Journal of high energy physics, 2013)
Abstract: The determination of the differential branching fraction and the first angular analysis of the decay B0s → ϕμ + μ − are presented using data, corresponding to an integrated luminosity of 1.0 fb−1, collected by the LHCb experiment at s√=7TeV. The differential branching fraction is determined in bins of q 2, the invariant dimuon mass squared. Integration over the full q 2 range yields a total branching fraction of B(B0s→ϕμ+μ−)=(7.07+0.64−0.59±0.71±0.71) × 10−7, where the first uncertainty is statistical, the second systematic, and the third originates from the branching fraction of the normalisation channel. An angular analysis is performed to determine the angular observables F L, S 3, A 6, and A 9. The observables are consistent with Standard Model expectations.
Im Titel sind "0", "+" und "-" hochgestellt und "s" tiefgestellt
LHCb Collaboration: R. Aaij, C. Abellan Beteta, B. Adeva, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 600
Gesehen am 21.04.2021